Physical exercise interventions for people with Parkinson's disease: a bibliometric review of systematic reviews - Sinval Adalberto Rodrigues-Junior; Cristiano Padilha; Renan Souza; Clodoaldo Antônio de Sá (Brazilian Society of Geriatrics and Gerontology, 2023)
This bibliometric study aimed to characterize published systematic reviews assessing the effects of physical exercise on people with Parkinson's disease. Eligible studies were searched in Web of Science, Scopus, Cochrane Library, and MEDLINE via PubMed databases. No date or language restrictions were applied. Studies were selected based on the inclusion criteria, and the results were uploaded to Bibliometrix 4.0 for R for bibliometric analysis. A total of 146 studies were included in the analysis, with the first one having been published in 2005. The annual growth rate was 14.72%, with an average publication time of 3.72 years. Themes based on indexed keywords represented elements of the PICO question, namely Parkinson's disease, exercise, therapy, rehabilitation, and outcomes such as gait, balance, and quality of life. A considerable number of systematic reviews addressing the effects of physical exercise interventions on people with Parkinson's disease have been published since the mid-2000s. Systematic reviews were first published by countries with long-established older populations. Exercise-based interventions and their effects on gait, balance, and quality of life in people with Parkinson's disease have been the focus of the most recent reviews.